Fullerene-free organic solar cells with an efficiency of 3.7% based on a low-cost geometrically planar perylene diimide monomer - Singh, R.; Aluicio-Sarduy, Eduardo; Kan, Z.; Ye, T.; Mackenzie, R. C.I.; Keivanidis, Panagiotis E. (My University, 2014)
The aggregate-induced limitation for high power-conversion efficiencies (PCEs) of perylene-diimide (PDI):polymer solar cells can be circumvented when two simple rules are respected; the aggregate size of PDI remains short enough and the omnipresent PDI aggregates are electronically interconnected. Following these guidelines, a PCE of 3.7% is delivered by using the solution-processable, planar PDI monomer of N,N′-bis(1-ethylpropyl)-perylene-3,4,9,10- tetracarboxylic diimide as the electron acceptor mixed with the low-energy gap polymeric donor poly[(4,8-bis(5-(2-ethylhexyl)thiophen-2-yl)-benzo[1,2-b;4,5- b′]dithiophene)-2,6-diyl-alt-(4-(2-ethylhexanoyl)-thieno[3,4-b]thiophene)) -2,6-diyl] (PBDTTT-CT). The PBDTTT-CT:PDI composite absorbs strongly the light in the region of 400 nm-800 nm and after adding a small amount of 1,8-diiodooctane (DIO) efficient photocurrent generation is achieved. Space-charge limited dark current and transient photovoltage measurements suggest that the use of the DIO component optimizes the electron/hole carrier mobility ratio, suppresses the non-geminate recombination losses and improves the charge extraction efficiency. © the Partner Organisations 2014.